Cuidado como sustentação da vida : narrativas de jovens que convivem com adoecimentos crônicos raros - Souza, Ítala Paris de (2023)
This thesis approaches the biographies of people who live with a rare chronic illness, lay specialists, active in the fight for the recognition of rights and who encourage us to think about a fundamental aspect of our lives: care. The objective was to understand how care is configured in cases of rare chronic illnesses based on the experience of young adults who (coexist) live in such conditions. Of a qualitative nature, it joins the socio-anthropological perspective, using Paul Ricoeur's phenomenology to cover the points of view of the subjects in their experience, combined with Joan Tronto's ethics of care, which is guided by democratic principles. The discussion is pertinent given the scarce production on the subject in the Brazilian and world scenario, mainly regarding ethics and morals in rarity, adding, still, to the principles of justice and democracy from the perspective of Collective Health. These are two people diagnosed with rare syndromes, namely: a 28-year-old with Machado Joseph Disease (DMJ) and a 23- year-old with Tourett Syndrome. Data production took place through biographical interviews, interactions and consultations in virtual environments and journalistic headlines, from 2020 to 2022. The corpus of analysis with oral reports, observations and notes on virtual pages composed the 220 pages of empirical material. The analysis placed care in a heterogeneous network of interrelationships involving people, institutions (family, State, market, social/virtual networks), organizations, resources, knowledge and practices; producer of complex situations not restricted to the private environment, but encompassing the collective and institutionalized. The results were organized into six topics that, despite their rarity, show common or similar aspects and the singularities of each case. It begins by introducing the interlocutor, followed by the presentation of the discovery process with the respective repercussions of the formal diagnosis, prognosis and living with the referred syndromes, in which stigmatization stands out. Separately, the specificities of each case and the care they require are treated, showing knowledge modeled according to the peculiar needs and improved over time and attentive to the details of what ordinarily matters. One topic problematizes feminized care, especially in one of the cases, showing the female overload and the moralities involved that impel them to assume care and its material and immaterial costs. Another encompasses the non-passivity of people when seeking complex interventions accessed via judicialization. It ends by discussing the displacement of the experience to the collective space through activism in digital social networks, configuring it as collective care. The delicate and meticulous care, based on sensitivity to the details that matter in everyday life, transcends the purely biophysical dimension. It encompasses elements such as respect, welcome, dialogue and attentive listening. Recognizing the diversity, tensions and contradictions inherent to care allows us to build solid and fertile bases to promote public policies that consecrate care as a fundamental right. In this sense, it is essential to contemplate the gender perspective and collective responsibility, aligning with a society that aims to be fair and democratic.